A regulatable adenovector system for GDNF and GFP delivery in the rat hippocampus. (October 2020) - Coll, Lucía; Rodriguez, Silvia S.; Goya, Rodolfo G.; Morel, Gustavo R.
Abstract: Spatial memory performance declines in both normal aging and Alzheimer's disease. This cognitive deficit is related to hippocampus dysfunction. Gene therapy using neurotrophic factors like Glial cell line-derived neurotrophic factor (GDNF) emerges as a promising approach to ameliorate age-related cognitive deficits. We constructed a two vector regulatable system (2VRS) which consists of a recombinant adenoviral vector (RAd) harboring a Tet-Off bidirectional promoter flanked by GDNF and Green Fluorescent Protein (GFP) genes. A second adenovector, RAd-tTA, constitutively expresses the regulatory protein tTA. When cells are cotransduced by the 2VRS, tTA activates the bidirectional promoter and both transgenes are expressed. In the presence of the antibiotic doxycycline (DOX) transgene expression is silenced. We tested the 2VRS in CHO-K1 cells where we observed a dose-dependent GFP expression that was completely inhibited by DOX (1 mg/ml). The 2VRS injected in the hippocampal CA1 region transduced both neurons and astrocytes and was efficiently inhibited by DOX added to the drinking water. In order to assess GDNF biological activity we injected 2VRS and its Control (CTRL) vector in the hypothalamus and monitored body weight for one month. The results showed that GDNF retards weight recovery 6 days more than CTRL. In conclusion, our 2VRS demonstrated optimal GFP expression and showed a bioactive effect of transgenic GDNF in the brain.